2017
DOI: 10.1021/acsami.7b11795
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Engineering with Cross-Linkable Fullerene Derivatives for High-Performance Perovskite Solar Cells

Abstract: Two fullerene derivatives with styryl and oxetane cross-linking groups served as interfacial materials to modify an electron-transporting layer (ETL) of TiO, doped with Au nanoparticles, processed under low-temperature conditions to improve the performance of perovskite solar cells (PSC). The cross-linkable [6,6]-phenyl-C-butyric styryl dendron ester was produced via thermal treatment at 160 °C for 20 min, whereas the cross-linkable [6,6]-phenyl-C-butyric oxetane dendron ester (C-PCBOD) was obtained via UV-cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…The ratio of PMMA to PCBM was found to be critical for achieving high PCE and from the optimal ratio of PMMA:PCBM = 1:3 the PCE was increased from 19.6% to 20.4% (Figure b) and the hysteresis was thoroughly suppressed (Figure c,d). Except for PCBM, other fullerene derivatives (such as C‐PCBOD, C‐PCBSD, and PCBB‐2CN‐2C8) were also developed to modify the perovskite/TiO 2 interface . Graphene is also candidate, where Zhao et al reported the modification of SnO 2 with graphene modified chemically by N , N ′‐bis‐[2‐(ethanoic acidsodium)]‐1,4,5,8‐naphthalene diimide (NDI) surfactant for normal planar PSCs.…”
Section: Interface Recombinationmentioning
confidence: 99%
“…The ratio of PMMA to PCBM was found to be critical for achieving high PCE and from the optimal ratio of PMMA:PCBM = 1:3 the PCE was increased from 19.6% to 20.4% (Figure b) and the hysteresis was thoroughly suppressed (Figure c,d). Except for PCBM, other fullerene derivatives (such as C‐PCBOD, C‐PCBSD, and PCBB‐2CN‐2C8) were also developed to modify the perovskite/TiO 2 interface . Graphene is also candidate, where Zhao et al reported the modification of SnO 2 with graphene modified chemically by N , N ′‐bis‐[2‐(ethanoic acidsodium)]‐1,4,5,8‐naphthalene diimide (NDI) surfactant for normal planar PSCs.…”
Section: Interface Recombinationmentioning
confidence: 99%
“…[ 28–37 ] The fullerene derivative acts to improve electron transfer at the TiO 2 /PSK interface by lowering the interfacial resistance, reducing the nonradiative recombination channels (trap/defect sites) at the interface, blocking holes, and increasing the surface hydrophilicity to deposit good‐quality PSK films. [ 28–33,33–37 ] Furthermore, it was also shown that the light‐soaking instability of PSCs mainly originates from charge accumulation at the TiO 2 /PSK interface, which can be eliminated by interfacial modifications with a layer of fullerene. [ 33 ] Therefore, inserting an interlayer of fullerene between the TiO 2 ETL and PSK can also improve the long‐term stability of the cell.…”
Section: Resultsmentioning
confidence: 99%
“…[ 51 ] Likewise, cross‐linkable [6,6]‐phenyl‐C 61 ‐butyric styryl dendron ester (c‐PCBSD) was also demonstrated in regulating interfacial energy as well as electronic quality of perovskite layers, contributing to high efficiency, fully solution‐processed and flat junction solar cell. [ 52 ] Amassian et al further deposited a mesostructured cross‐linking PCBM on the mesoporous TiO 2 layer, which can both enhance the structural and electronic properties of the perovskite layer grown atop. [ 53 ] More importantly, the cross‐linking strategy conduced to the long‐term stability of fullerene ETLs by inhibiting morphological changes and aggregation of fullerenes.…”
Section: Functionalized Fullerenes For Regular Structure Pscsmentioning
confidence: 99%